Debt Maturity and the International Financial Architecture - Jeanne, Olivier (Washington, D.C. : International Monetary Fund, 2004)
This paper presents a theory of the maturity of international sovereign debt and derives its implications for the reform of the international financial architecture. It presents a general equilibrium model in which the need to roll over external debt disciplines the policies of debtor countries but makes them vulnerable to unwarranted debt crises owing to bad shocks. The paper presents a welfare analysis of several measures that have been discussed in recent debates, such as the adoption of renegotiation-friendly clauses in debt contracts and the establishment of an international bankruptcy regime for sovereigns.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet